Urinary Lactate Dehydrogenase Activity and Its Isozyme Patterns in Kawasaki Disease. (28th February 2017) - Kawamura, Yoichi; Takeshita, Seiichiro; Kanai, Takashi; Takizawa, Mari; Yoshida, Yusuke; Tsujita, Yuki; Nonoyama, Shigeaki
Abstract : Abnormal urinary findings, such as sterile pyuria, proteinuria, and microscopic hematuria, are often seen in the acute phase of Kawasaki disease (KD). We investigated the potential significance of urinary lactate dehydrogenase (U-LDH) activity and its isozyme patterns in KD. Total U-LDH activity and its isozymes (U-LDH1-5) levels were compared among 120 patients with KD, 18 patients with viral infection (VI), and 43 patients with upper urinary tract infection (UTI) and additionally compared between intravenous immunoglobulin (IVIG) responders (n = 89 ) and nonresponders (n = 31 ) with KD. Total U-LDH activity was higher in KD (35.4 ± 4.8 IU/L, P < 0.05 ) and UTI patients (66.0 ± 8.0 IU/L, P < 0.01 ) than in VI patients (17.0 ± 6.2 IU/L). In the isozyme pattern analysis, KD patients had high levels of U-LDH1 and U-LDH2, while UTI patients had high levels of U-LDH3, U-LDH4, and U-LDH5. Furthermore, IVIG nonresponders of KD had significantly higher levels of total U-LDH activity (45.1 ± 4.7 IU/L, P < 0.05 ), especially U-LDH1 and U-LDH2 (P < 0.05 ), than IVIG responders (32.0 ± 2.8 IU/L). KD patients have increased levels of total U-LDH activity, especially U-LDH-1 and U-LDH2, indicating a unique pattern of U-LDH isozymes different from that in UTI patients.